(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses one of the most pressing issues in the field of translation, the manifestation and important aspects of the skill of a translator in literary translation. In this case, the author’s style of expression, the spirit of national identity of the period is reflected in the translation through examples. In addition, important aspects of figurativeness and its translation in a work of art are illustrated. The translator’s word choice skills are mentioned here.